Transcarotid: A sign from above? - Eng, Marvin H.; Fang, H. Kenith (Catheterization and cardiovascular interventions, 2021)
Key Points Transcarotid (TC) access is primarily being performed in high risk patients and early mortalities are likely due to comorbidities. Otherwise, transcarotid access has low rates of vascular complications and perioperative strokes. The length of stay and rates of major bleeding should be targeted as areas for improvement.